Parotid Oncocytoma as a Manifestation of Birt-Hogg-Dubé Syndrome - Kazuki Yoshida; Masao Miyagawa; Teruhito Kido; Kana Ide; Yoshifumi Sano; Yoshifumi Sugawara; Hiroyuki Takahata; Nobuya Monden; Mitsuko Furuya; Teruhito Mochizuki (Case Reports in Radiology)
Birt-Hogg-Dubé syndrome (BHD) is a rare autosomal dominant disease characterized by skin fibrofolliculomas, pulmonary cysts, spontaneous pneumothoraces, and renal cancers. Oncocytomas are benign epithelial tumors that are also rare. Recently, there have been a few case reports of BHD with a parotid oncocytoma that appears to have a BHD phenotype. Here we document the eighth known case and describe the magnetic resonance imaging features of the parotid oncocytoma, which mimicked Warthin’s tumor. Radiologists should be aware of the association between these rare disorders.